1998
DOI: 10.1007/bf02345101
|View full text |Cite
|
Sign up to set email alerts
|

Leveling the playing field: A report of the commonwealth fund task force on academic health centers

Abstract: Over the last 50 years, the nation's academic health centers (AHCs)--defined here as the 125 institutions that include at least a medical school and its closely affiliated clinical facilities and faculty practice plans--have come to serve a unique set of functions in the nation's health care system and in their communities. The AHCs produce a variety of health-related goods and services that have social value, but tend to be undervalued and undersupplied in competitive markets.These goods and services include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The dual missions of providing health care to a market as well as providing graduate education may put academic hospitals at a distinct competitive disadvantage to their nonacademic counterparts (Blumenthal, Campbell, and Weissman, 1997). Therefore, it is important to acknowledge these different organizational missions and classify each hospital accordingly.…”
Section: Teaching Hospitalmentioning
confidence: 99%
“…The dual missions of providing health care to a market as well as providing graduate education may put academic hospitals at a distinct competitive disadvantage to their nonacademic counterparts (Blumenthal, Campbell, and Weissman, 1997). Therefore, it is important to acknowledge these different organizational missions and classify each hospital accordingly.…”
Section: Teaching Hospitalmentioning
confidence: 99%
“…The result of changes in the research environment of academic medical centers has been demonstrated in investigations of the relationship between managed care penetration and research productivity. Since 1990, NIH research grant support has been growing less rapidly in AHCs in markets with high MCO enrollment than at institutions with low or moderate MCO penetration (Blumenthal & Thier, 1998). The amount of institutional support as a proportion of total funding is more than twice as high in less competitive markets compared with the most competitive markets (Weissman, Saglam, Campbell, et al, 1999).…”
Section: Health Systems Change and Clinical Researchmentioning
confidence: 99%
“…More than six million Medicare beneficiaries and half of Medicaid recipients are enrolled in managed care plans (Fox, 2001). At the same time, clinical research in academic health centers, the traditional site for conducting randomized clinical trials (RCTs), has declined (Blumenthal & Thier, 1998). The need for research to inform the larger, systems-based issues of the organization and delivery of primary care services has never been greater (Dudley, Landon, Rubin, et al, 2000; Institute of Medicine, 1996; McNeese-Smith & Nyamathi, 1999).…”
mentioning
confidence: 99%
“…There was limited assessment of the impact of the curriculum on outcomes for the learner or the patients they care for. Only 30% of 31 this may provide an opportunity for meaningful learning in the context of graduate medical education. Point of care teaching around health disparities and social determinants of health can be a powerful mechanism for residents to internalize these complex topics through the eyes of their own patients.…”
Section: Discussionmentioning
confidence: 99%